Dodging death or the illusion of peace as a symptom (1993)
The policy enacted by a community organization that sought for peace instead of war, dialogue instead of confrontation and mutual respect instead of abuse brought about a reaction that ended in the death of three of its leaders and of a journalist interested in social problems. This paper  analyzes the situation as an effect of a group relationship and explores the structural conditions of the individual that give strength to ties of such a nature.